The interchangeability of global positioning system and semiautomated video-based performance data during elite soccer match play - Harley, J. A.; Lovell, R. J.; Barnes, C. A.; Portas, M. D.; weston, M. (The Journal of Strength and Conditioning Research, 2011)
In elite-level soccer, player motion characteristics are commonly generated from match play and training situations using semiautomated video analysis systems and global positioning system (GPS) technology, respectively. Before such data are used collectively to quantify global player load, it is necessary to understand both the level of agreement and direction of bias between the systems so that specific interventions can be made based on the reported results. The aim of this report was to compare data derived from both systems for physical match performances. Six elite-level soccer players were analyzed during a competitive match using semiautomated video analysis (ProZone® [PZ]) and GPS (MinimaxX) simultaneously. Total distances (TDs), high speed running (HSR), very high speed running (VHSR), sprinting distance (SPR), and high-intensity running distance (HIR; >4.0 m·s-1) were reported in 15-minute match periods. The GPS reported higher values than PZ did for TD (GPS: 1,755.4± 245.4 m; PZ: 1,631.3 ± 239.5 m; p < 0.05); PZ reported higher values for SPR and HIR than GPS did (SPR: PZ, 34.1 ± 24.0 m; GPS: 20.3 ± 15.8 m; HIR: PZ, 368.1 ± 129.8 m; GPS: 317.0 ± 92.5 m; p < 0.05). Caution should be exercised when using match-load (PZ) and training-load (GPS) data interchangeably.